On domains that admit well-behaved strategy-proof social choice functions - Sanver, M. Remzi; Chatterji, Shurojit; Sen, Arunava (Academic Press Inc Elsevier Science, 2013)
In this paper, we investigate domains that admit "well-behaved" strategy-proof social choice functions. We show that if the number of voters is even, then every domain that satisfies a richness condition and admits an anonymous, tops-only, unanimous and strategy-proof social choice function, must be semi-single-peaked. Conversely every semi-single-peaked domain admits an anonymous, tops-only, unanimous and strategy-proof social choice function. Semi-single-peaked domains are generalizations of single-peaked domains on a tree introduced by Demange (1982) [13]. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Strategy-proofness; Restricted domains; Semi-single-peaked domains